Digitalisasi Hubungan Masyarakat Melalui Implementasi Pelayanan Publik Berbasis E-Government - Suhara, Rizki Budhi; Sapari, Yusuf; Laksana , Medika Oga (Jurnal Locus Penelitian dan Pengabdian, 2025)
Public Relations (PR) at the Communication and Information Service (Diskominfo) of Cirebon Regency in the Field of Information and Public Communication (IKP) has an important role in the progress of the development of e-Government services. The Public Relations of the Cirebon Regency Diskominfo is the party that provides materials (data and information) to be published to all people of Cirebon Regency. In addition, it has an important role in efforts to organize public service activities, provide information and communication, restructure relations with the community, foster relationships with other Regional Apparatus, and enable the transformation of society in the digital era. In optimizing the existence of Public Relations of the Cirebon Regency Diskominfo as an extension of the Regional Government, it has the responsibility to ensure that every public service provided is the best service and able to meet the expectations of the people of Cirebon Regency. The method in this study is qualitative as described. Using data sources in this study, namely primary data and secondary data. Primary data is the main data collected directly in the field as well as documentation studies. Primary data observation of the Cirebon Regency Communication and Information Office in Digital Public Relations activities through the development of e-Government. Secondary data is supporting data from various written literature related to the research topic. The results of this study outline that the use of websites and social media. The emergency services of the 112 call center and the adoption of Artificial Intelligence (AI) technology are long-term plans to improve the effectiveness of services. Furthermore, to provide the best experience for all people in Cirebon Regency. The cirebonkab.go.id website is the official website of the Cirebon Regency government one data portal operated by the Public Relations staff for Information and Public Communication. The Public Relations Officer has the task and responsibility of providing materials (data and information) obtained from various Regional Apparatus in Cirebon Regency to be published on the website. Then, coordinate with other fields of work, one of which is the Statistics, Cryptography, and e-Government Sector as parties who have duties and responsibilities in managing service data on the website. Evaluation activities are materials to analyze data on the performance of the services provided and to measure the level of community satisfaction in Cirebon Regency. In addition, it helps in identifying factors that can affect the implementation of service activities, both from internal and external agencies/institutions.